Context of Substance Use: Harm Reduction and Safer Supply - Haines, Marlene (Journal of drug issues, 2025)
Canada continues to be in the midst of an ongoing unregulated drug poisoning crisis, with over 40,000 opioid-related deaths since 2016. To develop a better understanding of the context of drug use, we interviewed safer supply program participants in Ottawa, Canada. Data collection included semi-structured interviews which were analyzed thematically. Overall, 2 major themes arose, which included 1) the historical and ongoing effects of trauma, and 2) a cycle of drug use that overwhelmed them. From this, a framework was created which depicts the context of substance use. Our research reinforced the importance of considering the historical and ongoing effects of trauma on the lives of people who use drugs when developing harm reduction and substance use programs. Further, participants found safer supply programs to be useful in disrupting a cycle of drug use they felt trapped in and allowed them a sense of autonomy regarding their drug use.